2021
DOI: 10.1038/s41598-021-01263-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum HE4 and CA125 combined to predict and monitor recurrence of type II endometrial carcinoma

Abstract: There is no recognized serum biomarker to predict the recurrence of endometrial carcinoma (EC). We aimed to explore serum human epididymis protein 4 (HE4) and cancer antigen 125 (CA125) as the biomarkers to predict and monitor recurrence of type II EC. 191 patients diagnosed with type II EC were involved for this retrospective study. Comparing recurrent with non-recurrent patients, HE4 levels resulted a statistically significant difference at primary diagnosis and recurrence, respectively (P = 0.002 and P = &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In clinical practice, CA125 has been routinely used to diagnose a variety of malignancies, especially epithelial ovarian cancer [ 28 ]. Quan et al [ 29 ] demonstrated that serum CA125 significantly correlated with clinicopathological risk factors, such as depth of myometrial invasion, LN status, and FIGO stage and that CA125 is a promising prognostic indicator for EC [ 30 , 31 ]. In our study, CA125 could be used as an independent predictor of PLNM in EC patients, which is consistent with the results of Lei et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, CA125 has been routinely used to diagnose a variety of malignancies, especially epithelial ovarian cancer [ 28 ]. Quan et al [ 29 ] demonstrated that serum CA125 significantly correlated with clinicopathological risk factors, such as depth of myometrial invasion, LN status, and FIGO stage and that CA125 is a promising prognostic indicator for EC [ 30 , 31 ]. In our study, CA125 could be used as an independent predictor of PLNM in EC patients, which is consistent with the results of Lei et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have mentioned the role of serum cancer antigen (CA)-125 in predicting EC [ 38 , 39 ]. Therefore, we hope to develop a better study design in order to provide predictive modeling of EC and cancer stage based on well-known clinical risk factors (body mass index, postmenopausal age, hypertension, and diabetes) combined with endometrial thickness, Doppler UtA indices, and CA-125 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flow chart of literature screening is shown in Figure 1. among these studies, eight were from China, [7][8][9][10][11][12][13][14] four from Italy, [15][16][17][18] four from Poland, [19][20][21][22] three from Iran, [23][24][25] two from Australia, 26,27 two from Czech Republic, 28,29 two from Egypt, 30,31 two from Thailand, 32,33 two from The Netherlands, 34,35 two from Turkey, 36,37 and one each was from America, Austria, Denmark, India, Ireland, Slovenia, and Spain. [38][39][40][41][42][43][44] Thirty-three studies described the relationship between serum HE4 levels and the clinicopathological characteristics of EC, three studies described the relationship between tissue HE4 expression and the clinicopathological characteristics of EC, and two studies examined HE4 expression in both samples.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%